Monitoring of changes in mineral and vitamin metabolism under the infl uence of feed additive in piglets with experimental associated mycotoxicosis - Andriichuk A.; Melnyk A.; Vovkotrub N. (Науковий вісник ветеринарної медицини, 2020)
Toxicobiological eff ect of mycotoxins association of the Penicillium and Fusarium fungus (T-2 toxin at a concentration of 0.1 mg/kg, fumonisin B1 ‒ 0.5 mg/kg, vomitoxin (DON) ‒ 0.1 mg/kg, penicillic acid ‒ 1 mg/kg) was accompanied by the development of a complex pathological process in weaned piglets. In this regard, the detoxifi cation and sorption capacity of the complex feed additive "Harufi x+" based on mannanoligosaccharides was studied. The additive eff ect on the resorptive activity of mineral and vitamin nutrients of feed under the normal feeding conditions and in case of contamination with mycotoxins has been studied. The use of enterosorbent off set the toxic eff ects of micromycete metabolites, which contributed to the growth of piglets. Thus, weight growth rate increase of the piglets in group 1 (i.e., those whose diet included the additive, unlike the diet of the animals in control group) constituted 16 %, while their average weight growth rate was high and constituted 1.96 kg per day. In addition, during the study of calcium, phosphorus, magnesium, ferum, zinc, copper and manganese in the piglets blood was not found excretion of these elements with a sorbent, moreover, noted the normalization their blood level. The study content of vitamins A and E, the same as with mineral nutrients, has not been established decrease during treatment with study the pharmaceutical. The obtained results testify the active absorption in the gastrointestinal tract of the vitamin components within the fodder combined with fodder additive “Harufi x+” and high biological accessibility of its transport forms. The effi ciency of the additive can be explained by its composition, namely the complex of mineral and organic components that are formed by modifi cation of the organic cations of the mineral surface.